Agricultural engineering activities in farming subsystems in St Lucia - Karandikar, Abhijit (CARDI CastriesLC, 1986)
Describes the designing, fabrication and testing of small farm implements (of an intermediate technology level) and drip irrigation kits on small farmers' holdings in St Lucia. Implements include the cult-a-eze in flatter terrains and lighter soil areas and roho cultivators which can be used as alternatives to the cutlass. Also examines the potential usefulness of two similarly designed peanut shellers and the `Hartley' fork.